Smart Free-Fall Experiment Apparatus Using Arduino, Infrared–Ultrasonic Sensors, and Bluetooth Data Logging - Jeli Hendra; Marjoni Imamora Ali Umar; Hadiyati Idrus; Artha Nesa Chandra (Edusainstika, 2025)
This study aims to develop a valid and practical Arduino Uno-assisted free fall experiment tool as a learning medium for 11th grade high school/MA physics. It uses the research and development method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of three expert validators and grade XI high school students as limited test subjects. The practical tool was developed by integrating Arduino Uno, infrared sensors, ultrasonic sensors, HC-05 Bluetooth modules, and MicroSD modules to support automatic time and height measurements, wireless data transmission, and digital storage of experimental data. Data collection was carried out using expert validation sheets and student practicality questionnaires, then analyzed using validity and practicality percentages based on predetermined criteria. The results of the study show that the developed laboratory equipment has a very high level of validity with an average percentage of 88% (very valid category) and a level of practicality of 81.5% (very practical category). These findings indicate that the practical tool is suitable for use as a physics learning medium and is capable of improving the quality of practical activities through more accurate measurements, time efficiency, and more systematic management of experimental data. Unlike previous studies, which generally focused on technical aspects in a partial manner, this study emphasizes the integration of measurement systems, data transmission, and digital data management in a single learning device.